(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the features of the development of political culture, the origin of the etymology of political culture, scientific and political views related to the process of its formation of political culture. The factors influencing the development of political culture, political consciousness, political experience, political behavior, levels, models and types of political culture are investigated. The concept and essence of legitimacy in political processes are revealed.